2015
DOI: 10.1021/acs.orglett.5b00282
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyzed Site-Selective C–H to C–C Conversion of Aliphatic Nitriles

Abstract: β- or γ-Site-selective C-H alkylation of aliphatic nitriles has been achieved using a decatungstate salt as the photocatalyst. The observed site selectivity was justified by a radical polar effect in transition states for hydrogen abstraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 43 publications
1
43
0
1
Order By: Relevance
“…This behavior has recently been exploited in the functionalization of aliphatic nitriles, in which a reactivity trend following the general rule CH >> CH 2 > CH 3 has been observed. As an example, the reaction between isocapronitrile ( 34 ) and acrylonitrile in the presence of TBADT (4 mol‐%) led to the formation of adduct 35 as the only product (73 % yield; Scheme ) . Curiously, the decatungstate anion could be conveniently incorporated into the pores of a copper‐based metal‐organic framework (MOF).…”
Section: Direct Hat Approachesmentioning
confidence: 99%
“…This behavior has recently been exploited in the functionalization of aliphatic nitriles, in which a reactivity trend following the general rule CH >> CH 2 > CH 3 has been observed. As an example, the reaction between isocapronitrile ( 34 ) and acrylonitrile in the presence of TBADT (4 mol‐%) led to the formation of adduct 35 as the only product (73 % yield; Scheme ) . Curiously, the decatungstate anion could be conveniently incorporated into the pores of a copper‐based metal‐organic framework (MOF).…”
Section: Direct Hat Approachesmentioning
confidence: 99%
“…In 2014, a highly selective β‐C−H alkylation and acylation of cyclopentanones using tetrabutylammonium decatungstate (TBADT) as a photocatalyst was reported by the research group of Fagnoni . In continuation of their interest in site‐selective functionalization, these authors reported the β‐ or γ‐site‐selective C−H alkylation of aliphatic nitriles using TBADT as a photocatalyst . A variety of aliphatic nitriles 59 gave the corresponding products 61 in moderate to good yields upon treatment with electron‐deficient alkenes 60 photocatalyzed by TBADT using a Xe lamp (300 W) through a Pyrex tube (Scheme ).…”
Section: C(sp3)−h Bond Functionalizationmentioning
confidence: 99%
“…49 We became curious about the effect imparted by a given functionality on an alkane scaffold in terms of site-selectivity in the CH cleavage reaction promoted by TBADT. 5 Consequently, we were able to find notable site-selectivity for a variety of ketones, 6,7 esters, 7 nitriles, 8 and alkylpyridines, 9 in which the S H 2 (bimolecular homolytic substitution) transition states between CH bond and decatungstate anion are highly influenced by radical polar and steric effects, rendering the functionalization of C(sp 3 )H bonds site-selective in each case. For example, β-selective CH to CC conversion of 3,3-dimethylcyclohexanone was achieved using TBADT as a photocatalyst (Scheme 1), 7 in which the lack of any α-CH functionalization was rationalized by the mismatched polar S H 2 transition state for α-CH cleavage, while the lack of γ-CH functionalization was due to the steric hindrance by the two methyl groups attached at the adjacent carbon of the targeted methylene group.…”
mentioning
confidence: 92%